Stability of an Additive-Cubic-Quartic Functional Equation in Multi-Banach Spaces - Zhihua Wang; Xiaopei Li; Themistocles M. Rassias (Abstract and Applied Analysis)
We prove the Hyers-Ulam stability of the additive-cubic-quartic functional equation in multi-Banach spaces by using the fixed point alternative method. The first results on the stability in the multi-Banach spaces were presented in (Dales and Moslehian 2007).